Developing a Tailored Texting Preventive Intervention: A Card Sort Methodology. Issue 2 (19th April 2017) - Braciszewski, Jordan M.; Tran, Tanya B.; Moore, Roland S.; Bock, Beth C.; Tzilos, Golfo K.; Chamberlain, Patricia; Stout, Robert L.
Abstract : Purpose: Intervention content written by adults for youth can result in miscommunication due to generational and cultural differences. Inviting at‐risk youth to participate in the creation of intervention material can augment acceptability for their peers. Methods: To improve intervention messaging, this study examines the utility of a card sort technique when creating cellular phone text messages to be used in a preventive substance‐use intervention. During focus groups with 24 youths who are exiting the foster care system—a population with distinct cultural attributes—participants were asked to rate stage of change‐specific health messages rooted in Motivational Interviewing and the Transtheoretical Model. Results: Participants unanimously favored content that encouraged autonomy and choice. Statements that invited a "look to the future" were also rated favorably. Messages that referenced the past were not rated well, as were suggestions for professional assistance. Finally, encouragement to receive social support for change was met with ambivalence. While some participants regarded support as helpful, many others felt a severe lack of support in their lives, possibly prompting further substance use. Conclusions: Youth exiting foster care constitutes a unique population whose voice is paramount in the development of interventions. The content present in traditional approaches to substance‐use prevention (e.g., increasing social support) may not apply to this group of vulnerable youth. The card sort technique has strong potential to evoke youth‐specific intervention content that is more readily understood and accepted by target audiences. Intervention content written by adults for youth can result in miscommunication due to generational and cultural differences. Co‐creation, rather, can augment acceptability. We examined the utility of a card sort technique when creating text messages for a preventive substance use intervention. Twenty‐four youth exiting foster care rated messages rooted in Motivational Interviewing and the Transtheoretical Model. Participants favored content that encouraged autonomy or "looking forward." Messages about the past and suggestions for professional assistance were rated poorly. Encouragement to rely on social support was met with ambivalence, as some felt discouraged that they lacked supports. The voice of foster youth is paramount for intervention development. This technique has strong potential to evoke content that is more readily understood and accepted.